Maps and Circulations: A Way of Expanding Biennials through Time and Space? - Anita Orzes (Index Journal)
This article proposes an act of remembering, shifting its focus away from the physical exhibition space to concentrate on the exhibition's broader context. In particular, this paper aims to explore what new perspectives the analysis of the circulation of ideas and people and the use of maps can contribute to the study of biennials. A biennial is envisaged as an exchange zone where heterogeneous networks intersect, merge, or confront and create maps of relationships. Giving visibility to these networks through map-making enables us to articulate dense multidirectional plots in the history of biennials and to trace a transnational history of complex geographies, relationships, and overlapping cartographies. With this in mind, this article analyses materials produced during the first three editions of the Havana Biennial (1984–1989). Employing geospatial visualisations and the study of currents of thought, this investigation shows a complex map of institutional, professional, and personal relationships that connected the Havana Biennial with other artistic events in Latin America. Likewise, this map of relations comes to “expand” our understanding of the Caribbean biennial, including other places, temporalities, agents, and mega-exhibitions—the knowledge provides valuable tools to see and understand the biennial from a wider perspective.